Clinical performance validation of the STANDARD G6PD test: A multi-country pooled analysis. - Adissu,W; Brito,M; Garbin,E; Macedo,M; Monteiro,W; Mukherjee,SK; Myburg,J; Alam,MS; Bancone,G; Bansil,P; Pal,S; Sharma,A; et al. (PLoS Negl Trop Dis, 2023)
INTRODUCTION: Screening for G6PD deficiency can inform disease management including malaria. Treatment with the antimalarial drugs primaquine and tafenoquine can be guided by point-of-care testing for G6PD deficiency. METHODS AND FINDINGS: Data from similar clinical studies evaluating the performance of the STANDARD G6PD Test (SD Biosensor, South Korea) conducted in Bangladesh, Brazil, Ethiopia, India, Thailand, the United Kingdom, and the United States were pooled. Test performance was assessed in a retrospective analysis on capillary and venous specimens. All study sites used spectrophotometry for reference G6PD testing, and either the HemoCue or complete blood count for reference hemoglobin measurement. The sensitivity of the STANDARD G6PD Test using the manufacturer thresholds for G6PD deficient and intermediate cases in capillary specimens from 4212 study participants was 100% (95% Confidence Interval (CI): 97.5%-100%) for G6PD deficient cases with <30% activity and 77% (95% CI 66.8%-85.4%) for females with intermediate activity between 30%-70%. Specificity was 98.1% (95% CI 97.6%-98.5%) and 92.8% (95% CI 91.6%-93.9%) for G6PD deficient individuals and intermediate females, respectively. Out of 20 G6PD intermediate females with false normal results, 12 had activity levels >60% on the reference assay. The negative predictive value for females with G6PD activity >60% was 99.6% (95% CI 99.1%-99.8%) on capillary specimens. Sensitivity among 396 P. vivax malaria cases was 100% (69.2%-100.0%) for both deficient and intermediate cases. Across the full dataset, 37% of those classified as G6PD deficient or intermediate resulted from true normal cases. Despite this, over 95% of cases would receive correct treatment with primaquine, over 87% of cases would receive correct treatment with tafenoquine, and no true G6PD deficient cases would be treated inappropriately based on the result of the STANDARD G6PD Test. CONCLUSIONS: The STANDARD G6PD Test enables safe acce